Incorporating Sustainable Practice in Mechanics and Structures of Materials 2010
DOI: 10.1201/b10571-80
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation into gomuti fibres/polyester composites

Abstract: In this study, gomuti fibres/polyester composites are examined for tensile and flexural properties. The specimens are produced by hand lay-up method for practicality. Fibre forms are in four variations that are random original layout, chopped random, unidirectional and woven mat. The fibres are not chemically treated for the purpose to initially evaluate and determine the properties of untreated gomuti fibres/polyester composites. Results showed that specimens with unidirectional orientation have the highest a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 9 publications
1
29
0
1
Order By: Relevance
“…The tensile strength of these composites is higher than the neat epoxy resin reported in Sastra et al 31 Gomuti/polyester composites with 10% fibre by weight as reported in Ticoalu et al 33 obtained lower tensile strength, approximately 8-70% of the strength of the typical neat polyester resin. 36 Similarly, Misri et al 34 reported that the strength of gomuti/polyester with 18% fibre fraction by weight was 19.21 MPa.…”
Section: Tensile Propertiesmentioning
confidence: 78%
See 2 more Smart Citations
“…The tensile strength of these composites is higher than the neat epoxy resin reported in Sastra et al 31 Gomuti/polyester composites with 10% fibre by weight as reported in Ticoalu et al 33 obtained lower tensile strength, approximately 8-70% of the strength of the typical neat polyester resin. 36 Similarly, Misri et al 34 reported that the strength of gomuti/polyester with 18% fibre fraction by weight was 19.21 MPa.…”
Section: Tensile Propertiesmentioning
confidence: 78%
“…33 The composites containing woven fibre has the highest flexural strength, followed by the composites with unidirectional, random and chopped fibre. However, gomuti/polyester composite specimen with chopped fibre has the highest flexural modulus.…”
Section: Flexural Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The tensile properties of sugar palm fibre/epoxy composites were summarised in [10]. It shows that the woven type composites demonstrated better performance compared to other type of fibres.…”
Section: Resultsmentioning
confidence: 99%
“…Fiber composite materials such as glass fiber, carbon fiber, and aramid have been widely used in automotive, marine, aerospace, aircraft industries, and are now being used in structural and infrastructure application such as windmill, roof, bridge, girder, railway sleepers, and floating river walkway . Because of their excellent tensile, toughness and thermal resistance properties, and their hydrophobic nature, composite has variety of applications.…”
Section: Introductionmentioning
confidence: 99%